Strategi Kepala Madrasah Perempuan dalam Melakukan Perubahan - Arif Mansyuri; Muhammad Nuril Huda (Proceedings of Annual Conference for Muslim Scholars, 2018)
This study was conducted to explain the strategy of woman principal in private Islamic junior high school (Madrasah Tsanawiyah Swasta) in making a change in madrassah. The study used a qualitative approach, with multisite design and Modified Analytic Induction. The study was conducted in three private MTs in Malang Regency, namely in MTs NU Pakis, MTs Al Huda Wajak, and MTs Hasyim Asy’ari Turen. The results of the study indicated the various changes that occured during the leadership of women principal, including governance changes, equipment changes, structural changes and cultural changes. in leading the changes at madrasah, women principal used strategies to achieve goals, strategies to manage conflict and strategic to make decision.